The most frequently used words: Comparing child-directed speech and young children's speech to inform vocabulary selection for aided input. (3rd April 2019) - Quick, Nancy; Erickson, Karen; Mccright, Jacob
Abstract: Transactional theories of communication development focus on the interplay among child, caregiver, and environmental variables. Typically, this interplay involves symmetry between receptive and expressive modes (i.e., speech), but is asymmetrical for children with complex communication needs who hear speech but use graphic symbols expressively. Aided input, during which a communication partner points to graphic symbols while talking, may increase symmetry, but it is challenging to determine which words to represent with graphic symbols to ensure adequate aided input is provided. In this study, secondary analysis of transcripts of 16 mothers who interacted with their children with typical development across six time points (between 9 and 15 months) revealed 267 words that comprised 80% of the 257, 480 words the mothers used. This list of words that mothers used most frequently was compared to three existing lists of the expressive vocabulary used most frequently by 65 toddlers and preschoolers with typical development, indicating substantial overlap. The results suggest that there is a common set of frequently occurring words that mothers use in their daily interactions with infants and toddlers, and that these same words also comprise a significant proportion of the words most frequently used by young children. Implications for representing these frequently occurring words with graphic symbols on the communication systems of children with complex communication needs are discussed.